Common and Potentially Prebiotic Origin for Precursors of Nucleotide Synthesis and Activation - Fahrenbach, Albert C. (J Am Chem Soc, 2017)
[Image: see text] We have recently shown that 2-aminoimidazole is a superior nucleotide activating group for nonenzymatic RNA copying. Here we describe a prebiotic synthesis of 2-aminoimidazole that shares a common mechanistic pathway with that of 2-aminooxazole, a previously described key intermediate in prebiotic nucleotide synthesis. In the presence of glycolaldehyde, cyanamide, phosphate and ammonium ion, both 2-aminoimidazole and 2-aminooxazole are produced, with higher concentrations of ammonium ion and acidic pH favoring the former. Given a 1:1 mixture of 2-aminoimidazole and 2-aminooxazole, glyceraldehyde preferentially reacts and cyclizes with the latter, forming a mixture of pentose aminooxazolines, and leaving free 2-aminoimidazole available for nucleotide activation. The common synthetic origin of 2-aminoimidazole and 2-aminooxazole and their distinct reactivities are suggestive of a reaction network that could lead to both the synthesis of RNA monomers and to their subsequent chemical activation.